Genotype-phenotype map characteristics of an in silico heart cell - Vik, Jon Olav; Gjuvsland, Arne B.; Li, Liren; Tøndel, Kristin; Niederer, Steven; Smith, Nicolas; Hunter, Peter; Omholt, Stig W. (Frontiers in Physiology, 2011)
Understanding the causal chain from genotypic to phenotypic variation is a tremendous challenge with huge implications for personalized medicine. Here we argue that linking computational physiology to genetic concepts, methodology and data provides a new framework for this endeavor. We exemplify this causally cohesive genotype-phenotype (cGP) modeling approach using a detailed mathematical model of a heart cell. In silico genetic variation is mapped to parametric variation, which propagates through the physiological model to generate multivariate phenotypes for the action potential and calcium transient under regular pacing, and ion currents under voltage clamping. The resulting genotype-to-phenotype map is characterized using standard quantitative genetic methods and novel applications of high-dimensional data analysis. These analyses reveal many well-known genetic phenomena like intralocus dominance, interlocus epistasis and varying degrees of phenotypic correlation. In particular, we observe penetrance features such as the masking/release of genetic variation, so that without any change in the regulatory anatomy of the model, traits may appear monogenic, oligogenic or polygenic depending on which genotypic variation is actually present in the data. The results suggest that a cGP modeling approach may pave the way for a computational physiological genomics capable of generating biological insight about the genotype-phenotype relation in ways that statistical-genetic approaches cannot.